Dominican Republic : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
In this paper, statistical data for the Dominican Republic were presented as real, public, financial, and external sectors. In real sector, GDP by sector at constant prices, savings, investment, consumer price index, petroleum statistics, and so on, were outlined. The public sector summarizes operations of the consolidated public sector, central government, and revenues. A summary of the banking system, claims, interest rates, financial indicators, and reserve requirements were described in the financial sector. In external sector, exports, imports, exchange rates, balance of payments, and net international reserves were listed.